Intrinsic labelling of common beans with 2H2O to enable estimates of protein digestibility - Pfrimer, Karina; Botelho Ferraz Branco, Roberto; Preston, Tom; Salles, Márcia SV; Roma-Junior, Luiz C.; Ferriolli, Eduardo (Isotopes in environmental and health studies, 2023)
Background: The use of plant protein intrinsically labelled with stable isotopes provides an innovative solution to assess the efficiency of protein intake by humans. Here, the incorporation of 2 H has been applied to intrinsically labelled plant protein in the common bean. This study aimed to evaluate which is the best phenological phase of seed maturation to incorporate the heavy hydrogen isotope 2 H into seed amino acids. Common beans (Phaseolus vulgaris L.) were grown in pots, then, after 50 days sowing, 2 H 2 O dissolved in irrigation water was applied, then again at an interval of either 3, 6, 9, and 12 days. Results: Applications of 2 H 2 O at 6, 9, and 12 days after the first application, in the full-flowering stage, were the best treatments for enriching protein-bound amino acids in the bean seed with 2 H. Conclusion: All treatments resulted in enrichment above 500 ppm, so the treatments (quantity and timing of 2 H 2 O addition) were deemed successful for enriching bean seeds. This makes the intrinsically labelled seeds suitable for preparing test meals to assess the digestion and essential amino acid absorption of common bean amino acids in human subjects.